Les Répercussions De La Crise Covid-19 Sur La performance financière des banques publiques algériennes selon le modèle de DuPont 2017-2021 - Djaouti Samir; Asmaa sofiane; Belhadj hocine (Journal of North African Economies, 2025)
The aim of this study is to analyze the financial performance of public banks in Algeria during the covid-19 crisis. Information was collected from financial statements and annual reports during the period (2017-2021). The modified DuPont model was used to measure the profitability of Algerian public banks, and classify them according to their performance. The study made it possible to draw up a classification which highlights the BEA as being the most efficient bank due to a better control of costs and the management of the assets, on the contrary the CNEP, the BADR and the BDL are positioned in bottom of the scale.